Localization of Epstein-Barr virus-encoded small RNAs by in situ hybridization. - Howe, J G (1986)
Human B lymphocytes latently infected with Epstein-Barr virus (EBV) synthesize two low molecular weight RNAs designated EBER 1 and 2. Using an in situ hybridization technique we have localized EBER 1 and 2 within the nucleus of single EBV-harboring B lymphocytes from established and recently transformed cell lines. As controls, the locations of the small nuclear RNA, U1, and the small cytoplasmic RNA, 7SL, were examined in HeLa and EBV-harboring cells. Because of possible functional similarities between EBERs and the adenovirus-associated (VA) RNAs, VAI was also localized; it appeared to be in the nucleus and cytoplasm, implying that VAI may have a different role than that of the nuclear-localized EBERs.